ANALISIS MOTIVASI KERJA DAN KINERJA PEGAWAI PADA KANTOR DINAS PEMUKIMAN DAN TENAGA KERJA KABUPATEN MIMIKA - Stepanus Sandy (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2022)
Each step of the organization in principle has a variety of needs that are immediately met. The diverse needs such as food, drink, clothing, shelter and also the need for appreciation. This need will be seen as a need that will raise employee morale, so as a leader must be able to provide direction that is linked to the motivation of subordinates so that they can achieve organizational goals. The purpose of this study is to find out how much work motivation and employee performance are and how the relationship between work motivation and employee performance at the Mimika Regency Settlement and Manpower Office. The method used is descriptive and associative methods with a quantitative approach. To measure work motivation using a Likers scale and to measure the relationship of work motivation to employee performance at the Mimika District Manpower Office using a correlation analysis tool (relationship). The results of the analysis show that most (45%) employees at the Mimika Regency Settlement and Manpower Office have work motivation in the fairly high category, and (40%) have performance in the fairly good category. While the relationship between work motivation and employee performance at the Mimika Regency Settlement and Manpower Office, the results of the analysis show that the relationship is very strong.